Crystal structure of dimethyl 3,12-dibenzyl-6,10-diphenyl-3,12-diazapentacyclo [6.3.1.02.7.04.11.05.9]-dodecane-7,11-dicarboxylate — acetone (2/1), C40H38N2O2 ⋅ 0.5C3H6O - Wang Ya-Nan (Zeitschrift für Kristallographie - New Crystal Structures, 2019)
C83H82N4O5, monoclinic, P21/c (no. 14), a = 21.705(8) Å, b = 18.455(6) Å, c = 17.774(7) Å, β = 112.216(6)°, V = 6591(4) Å3, Z = 4, Rgt(F) = 0.0647, wRref(F2) = 0.1531, T = 128 K.